Storage of halved strawberry fruits affects aroma, phytochemical content and gene expression, and is affected by pre-harvest factors - Baldwin, Ashley; Dhorajiwala, Rakhee; Roberts, Callum; Dimitrova, Simone; Tu, Sarah; Jones, Stephanie; Ludlow, Richard A.; Cammarisano, Laura; Davoli, Daniela; Andrews, Robert; Kent, Nicholas A.; Spadafora, Natasha D.; et al. (Frontiers in Plant Science, 2023)
Strawberry fruit are highly valued for their aroma which develops during ripening. However, they have a short shelf-life. Low temperature storage is routinely used to extend shelf-life for transport and storage in the supply chain, however cold storage can also affect fruit aroma. Some fruit continue to ripen during chilled storage; however, strawberries are a non-climacteric fruit and hence ripening postharvest is limited. Although most strawberry fruit is sold whole, halved fruit is also used in fresh fruit salads. To better understand the effects of cold storage, volatilomic and transcriptomic analyses were applied to halved Fragaria x ananassa cv. Elsanta fruit stored at 4 or 8 °C for up to 12 days over two growing seasons. The volatile organic compound (VOC) profile differed between 4 or 8 °C on most days of storage. Major differences were detected between the two different years of harvest indicating that aroma change at harvest and during storage is highly dependent on environmental factors during growth. The major component of the aroma profile in both years was esters. Over 3000 genes changed in expression over 5 days of storage at 8 °C in transcriptome analysis. Overall, phenylpropanoid metabolism which may also affect VOCs, and starch metabolism were the most significantly affected pathways. Genes involved in autophagy were also differentially expressed. Expression of genes from 43 different transcription factor (TF) families changed in expression: mostly they were down-regulated but NAC and WRKY family genes were mainly up-regulated. Given the high ester representation amongst VOCs, the down-regulation of an alcohol acyl transferase (AAT) during storage is significant. A total of 113 differentially expressed genes were co-regulated with the AAT gene, including seven TFs. These may be potential AAT regulators.